Peran Badan Permusyawaratan Desa Dalam PembuatanPeraturan Desa di Desa Bangun Kecamatan Parbuluan Kabupaten Dairi - Situmorang, Paulus R; Adam, Adam; Lubis, Yurial Arief (Universitas Medan Area, 2024)
This article or writing aims to explore the role of the Village Consultative Body (BPD) in the process of designing and making village regulations (Perdes) in Bangun Village, Parbuluan District, Dairi Regency and identify the obstacles faced by the BPD in carrying out village legislative functions and channeling community aspirations. The problem focuses on evaluating the role of the BPD in the process of making village regulations in Bangun Village. In order to approach this problem, a reference to the role theory put forward by Soejono Soekanto is used. Data was collected through observation, in-depth interviews, documentation and analyzed qualitatively. This study concludes that the role of the Village Consultative Body (BPD) in Bangun Village, Parbuluan District, Dairi Regency, is very important in making village regulations (Perdes). However, the implementation of BPD has not been optimal due to obstacles such as lack of understanding of regulations, poor communication and lack of training. To increase effectiveness, improvements in local government capacity, training and support are needed. With these steps, it is hoped that the BPD can be more effective in carrying out its functions and improve community welfare.